Medicinal chemistry handbook - Haldane, Thomas (New York, NY, USA NY Research Press, 2015)
This book contains researches based on medicinal chemistry and its sub-disciplines. The aim of this book is to provide an overview of recent issues and some significant advances in medicinal science. However, the major emphasis is on theoretical and experimental theories of modern drug designing, in order to help researchers, chemists, pharmaceutical specialists and chemical engineers in their future projects. This book will serve as a resource guide in the field of medicinal chemistry and facilitate the progress of this field.
Includes bibliographical references.
Keywords: Pharmaceutical chemistry -- Research